Implementation of Mobile Government in Banjar Negeri Village to Improve Services - Selnika, Dela (YHMM PUBLISHING, 2024)
Mobile Government is a government system that is made mobile-based so that the data can be accessed using Android phones. Meanwhile, in Banjar Negeri Village, the mobile government-based information system has not been adopted, so that in the process of serving the community it is still manual, this can slow down the administrative process and be less effective and efficient. That way, a mobile government-based digital information system is needed to improve services in Banjar Negeri Village. The data collection methods used are observation, literature study and observation. Meanwhile, the method of developing information systems in Banjar Negeri Village was built using the waterfall method. The results of the study show that the presence of the Mobile Government information system has reduced bureaucracy and accelerated the government administration process in Banjar Negeri Village. The public can apply for permits, access population information, and report problems through the easy-to-use mobile application. By implementing a mobile government-based information system, it is hoped that it can have a positive impact in improving services in Banjar Negeri Village. That way, the service process in Banjar Negeri Village can increase significantly.